Анализ энергетических характеристик ударных пневмоагрегатов со встроенным резервуаром - Атаманов, Ю. Л.; Крутиков, Геннадий Анатольевич; Стрижак, Марьяна Георгиевна (НТУ "ХПИ", 2014)
Викладена методика і результати аналізу енергетичних характеристик ударного ПА, що дозволяють виявити основні джерела непродуктивних енерговитрат і визначити в просторі безрозмірних критеріїв динамічної подоби область, що забезпечує найбільш ефективну реалізацію працездатності стисненого повітря.

The technique and the results of analysis of the energy characteristics of the shock PA, allowing to identify the main sources of energy and identify unproductive in the space of di-mensionless criteria of dynamic similarity region, providing the most efficient implementa-tion of compressed air efficiency.
Analysis of the energy characteristics of the shock pneumounit with integrated reservoir
Keywords: пневмоагрегаты; ударный пневмоцилиндр; сжатие воздуха; компрессоры; пневмоприводы